Stabilization of Expansive Soils using Alkali Activated Fly Ash (International Journal of Innovative Research in Engineering & Management, 2022)
Soil is one of fundamental components of  life. It supports life and human habitat. The human habitats  have evolved with advancement in science and technology.  Humans tend to increase their living standards by constructing large number of utilities and infrastructure to  accommodate their growing needs. Civil engineering has  reached its new heights consequently more challenges are  posed. Due to urbanisation and industrialisation population  of cities and towns is increasing. This has resulted in growing  networks of roads, rails and public places. Residential and  commercial infrastructures are also on demand. Interesting  thing to mention here is that all these activities are only  possible if the underlying strata of crust called soil is able to  withstand all these changes. Therefore the nature of soil on  which a foundation or pavement is constructed determines  the strength and durability of these structure. Interestingly  some waste materials like Fly Ash with suitable activators  may be use to make weak and expansive soils stable. By  adding these materials the chemical as well as physical  properties of the poor expansive soil can be suitably adjusted.  In this research work the use of sodium based alkaline  activators and fly ash as an additive in improving the  geotechnical characteristics of expansive soils is worked out.  Sodium hydroxide solutions 10, 12.5 and 15 molal with 1  Molar solution of sodium silicate were used as an activators.  In this mix the activator to ash ratio was kept between 1 and  2.5, and ash percentages of 20, 30 and 40%, relatively to the  total solids. Then it is tested by conducting the Unconfined  compressive strength UCS at curing peri ods of 3,7 and 28  days respectively and then it is compared with that of a  common fly ash based binder.
Keywords: Alkali Activated Expansive Soils; Fly Ash; Soil Stabilization; Unconfined Compressive Strength